Development Of Digital Teaching Materials For Mandarin Lessons At Sds Kristen Tabqha Batam - Soecipto Soecipto; Hesniati Hesniati (ConCEPt - Conference on Community Engagement Project, 2023)
This activity is aimed at compiling a digital teaching material that can be used to improve the quality of learning between teachers and students in schools, where the object of this activity is SDS Christian Tabqha Batam school which is an educational institution for elementary school level in Batam City. This school carries out a learning process that still uses teaching materials that are analog or non-digital so that the learning process is continuously stagnant to date. Therefore, in the period from September to December, this activity focuses on compiling digital teaching materials as a solution to improve and develop the quality of learning at SDS Christian Tabqha Batam school, especially for Mandarin subjects. The process of implementing this activity uses observation and interview methods in collecting data. As a result, this activity created outputs in the form of 6 student digital teaching materials which were divided according to the number of elementary levels in the form of powerpoint files. With this, it is hoped that SDS Christian Tabqha Batam can provide an even better learning process for its students, especially in Mandarin lessons. And finally, the recommendation for the future is to create digital teaching materials for all subjects contained in the curriculum at SDS Christian Tabqha Batam school so that the learning process as a whole can develop fully.